Fifteen years of HIV and syphilis outcomes among a prevention of mother‐to‐child transmission program in Haiti: from monotherapy to Option B+. Issue 7 (14th June 2018) - Deschamps, Marie Marcelle; Jannat‐Khah, Deanna; Rouzier, Vanessa; Bonhomme, Jerry; Pierrot, Julma; Lee, Myung Hee; Abrams, Elaine; Pape, Jean; McNairy, Margaret L.
Summary: Objective: To evaluate mother and infant outcomes in the largest prevention of mother‐to‐child‐transmission (PMTCT) programme in Haiti in order to identify gaps towards elimination of HIV and syphilis. Methods: Based on retrospective data from HIV+ pregnant women and their infants enrolled in PMTCT care from 1999 to 2014, we assessed maternal enrolment in PMTCT, receipt of antiretrovirals before delivery, maternal retention through delivery as well as infant enrolment in PMTCT, HIV testing and HIV infection. Four PMTCT programme periods were compared: period 1 (1999–2004, mono ARV), period 2 (2005–2009, dual ARV), period 3 (2010–2012, Option B) and period 4 (Oct 2012–2014, Option B+). Kaplan–Meier methods were used to assess retention in PMTCT care. Results: Among 4665 pregnancies, median age was 27 years and median CD4+ was 494 cells/μl (IQR 328–691). A total of 75% of women received antiretrovirals before delivery, and 73% were retained in care through delivery. Twenty‐two percent of women were lost before delivery, <1% died and 6% had stillbirths or abortions. Ninety‐four percent of infants who were born alive enrolled in PMTCT, of whom 92% had complete HIV testing. One hundred and sixty‐one infants were HIV+, giving a 5.4% HIV transmission rate (9.8%, 4.6%, 5.8% and 3.6% in periods 1–4). Retention among women through 12 months after PMTCT enrolment did not significantly differ across periods. However, among women who received antiretrovirals at the time of enrolment, retention 12 months later was lower in the Option B+ period (83%) than in periods 2 and 3 (94% and 93%) ( P  < 0.001). Syphilis infection among women decreased from 16% in period 1 to 8% in period 4, whereas syphilis testing of infants increased from 17% to 91%. Conclusion: Despite dramatic reductions in MTCT in Haiti, interventions are needed to improve retention to achieve MTCT elimination of HIV and syphilis.